Aptamer-based proximity labeling guides covalent RNA modification - Englert, Daniel; Matveeva, Regina; Sünbül, Murat; Wombacher, Richard; Jäschke, Andres (Chemical communications, 2021)
We describe the development of a proximity-induced bio-orthogonal inverse electron demand Diels-Alder reaction that exploits the high-affinity interaction between a dienophile-modified RhoBAST aptamer and its tetramethyl rhodamine methyltetrazine substrate. We applied this concept for covalent RNA labeling in proof-of-principle experiments.